A manifestação da loucura e do feminino na prosa de Conceição Evaristo - Azevedo, Tássia Vargas Escobar (2021)
This research aims to analyze the Afro-Brazilian novel Ponciá Vicêncio, by writer Conceição Evaristo, launched in 2003, taking into account female madness as a literary aspect. For that, we will use the philosopher Michel Foucault, in History of madness (2017), when referring to the terms “madness” and “power”, and the historian and feminist Margareth Rago, in The adventure of telling yourself. Feminisms, self-writing and inventions of subjectivity (2013), to elucidate the concept of “feminine”. Evaristo's work is marked by a female character, displaced and stigmatized by madness, manifested as a form of resistance and not alienation. Throughout the narrative, as a result of abandonment, the protagonist is supported by silence, with her memories, and starts to be considered crazy by her husband. However, the voice of the narrator will be responsible for exposing his thoughts, making explicit the subversive attitude of his speechlessness to the reader. The fragmented language and the circular narrative, where history, time and space are linked by the protagonist's memory, help to deconstruct the binary and hierarchical oppositions that support the patriarchy